An Empirical Study of Korean Adjectival Predicates that License Double Nominative Constructions*. (April 2015) - Nam, Jeesun
Despite the numerous studies proposed to explain double nominative constructions (DNCs) in Korean, empirical approaches to the predicate types that license their essential complements for conversion into nominatives have attracted little attention from scholars. However, given that, from syntactic and semantic viewpoints, the DNCs result from diverse and complex linguistic realities, a rigorous examination of the predicate types is required before attempting to elaborate theoretical assumptions further. Based on a large database of 6, 600 Korean adjectives, this study distinguishes two types of DNCs: Predicate-Dependent DNCs (PD-DNCs), where the two nominatives are essential arguments of the adjectival predicates; and Discourse-Dependent DNCs (DD-DNCs), where one of the two nominatives is not related to the argument structures, but either is generated by the split of one argument or is newly introduced at the discourse level. About 30% of the 6, 600 adjectives license PD-DNCs. On this basis, the current study provides two findings on PD-DNCs. First, adjectives licensing PD-DNCs are classified into five syntactic and semantic sub-types, the predominant complement type that is convertible into a nominative being that in -EY. Second, the adjectives licensing their complements for conversion into nominatives mostly show certain peculiar syntactic properties: most of them permit two syntactic constructions in a subject-complement crossing (SCC) relation like 'N1-NOM N2-POS ADJ-DEC = N2-NOM N1-POS ADJ-DEC'. With regard to DD-DNCs, in this study the DNCs are divided into four sub-types, which exhibit various semantic and syntactic properties that are distinct from those of PD-DNCs.